EARLY LEGAL STEPS OF EAST INDIA COMPANY - M. Ashraf Qureshi (International Journal of Contemporary Issues in Social Sciences, 2024)
From the earliest times of their existence all societies have had law. This is a self evident truth, which requires no proof. No society whether human or animal, can be conceived of without any norms for its organizations and operation. While the biologists are engaged in understanding the laws of animals’ world, social scientists, especially lawyers, have recorded from the very early times the laws that have regulated or guided human activity within the society. In the present context I am not interested in pursuing the discussion on the relationship between law and society. My concern is with legal history of India and particularly the earliest period of British being in the guise of Traders Company. Legal history of Indo-Pak can conveniently be studied under four important periods: Hindu period, Muslim period, British period and after independence. Hindu period extends for nearly 1500 years before and after the beginning of the Christian era. Muslim period begins with the first major invasion by Muslims in 1100 A.D. British period begins with the consolidation of British power in the middle of the eighteenth century and lasts for nearly two hundred years. The modern period began with the withdrawal of the British when on 14th August 1947, Pakistan was declared independent. However, in this article the early period of British is shortly dealt with that initially in 1600, how the East India Company affixed its steps by deceiving the Mughal Emperors in the guise of trade and business in India and lastly captured and controlled it in 1857 dramatically and left their cultural, social, political and legal effects in Indian society of which we are still slave.